LEGAL CERTAINTY OF THE JUDGE'S DECISION ON THE FATHER'S OBLIGATION TO PROVIDE FOR CHILDREN AFTER DIVORCE - Ansari, Ansari (International Conference on Humanity Education and Society (ICHES), 2024)
Children are the next generation of the nation, so their growth must be considered until they are adults. Even though the parents divorce, the parents are still responsible for all the needs and rights of the child. This study, using the type of research library research. The source of research data has three legal materials, primary, secondary, and tertiary. Data collection techniques include observation and study of documents. The data analysis process consists of three stages, data reduction, data presentation, and conclusion drawing or verification. The results of this study, the judge's legal findings use the method of legal construction with an argumentation analogy because there are no clear and firm rules about child support both in legislation and the Compilation of Islamic Law used by judges to decide a case. Instead, only jurisprudence governs on this issue. The judge rejected the claim to provide for the child because it was based on the decision of Supreme Court Jurisprudence Number 608 K / AG/ 2003, which stated that the obligation of a father to provide for his child is li intifa' and not li tamlik. Therefore, the negligence of a father who does not provide for his child cannot be sued.